EFEK KARDIOMETABOLIK GLUKOSA TINGGI, ASUPAN KUNING TELUR, PEMBATASAN KALORI, DAN PENCEMARAN UDARA PADA TIKUS - Diniwati Mukhtar; Aan Royhan; Hasna Luthfiah Fitriani; Melasari Marantika; Dita Safira Salsabila; Lena Fitriyana; Febri Irwansyah (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Background: Obesity is one of the cardiovascular disease risk factors that cause hypertrophy or hyperplasia of adipocytes. Changes in fat cells have the potential to increase inflammation and insulin resistance. Objective: This study aims to determine the effects of high glucose, egg yolk consumption, calorie restriction, and air pollution on body weight, cell size, and fat tissue weight in rats. Methods: The type of study is experimental and conducted for six weeks. Thirty white male rats were divided into five groups: sugar-treated group, egg yolk-treated group, restricted calorie intake-treated group, air pollutant-treated group, and control group. The cell size and weight of adipose tissue were obtained from abdominal and supraclavicular fat samples.Results: High glucose, egg yolk consumption, air pollution exposure, and calorie restriction were affected by increases in body weight, cell size, and adipose tissue mass (p < 0.05). The cell size and weight of adipose tissue have a negative effect on body mass index. Nevertheless, dietary intervention studies have shown that the size of fat cells decreases after calorie restriction-induced weight loss. Conclusion: The body weight, cell size, and adipose tissue weight of the rats were affected by a high sugar intake, egg yolk consumption, calorie restriction, and exposure to air pollution.